2017
DOI: 10.1016/j.jclinane.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation versus intravenous anaesthesia for adults undergoing on-pump or off-pump coronary artery bypass grafting: A systematic review and meta-analysis of randomized controlled trials

Abstract: There is high quality evidence that sevoflurane reduces death within 180 to 365days of surgery and, inotropic and vasoconstrictor support compared to propofol for patients undergoing coronary artery bypass grafting. There is also some evidence showing that the cardiac index is minimally influenced by administration of sevoflurane and desflurane compared to propofol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 73 publications
(193 reference statements)
0
23
0
1
Order By: Relevance
“…Nevertheless, there is clinical evidence showing that general anesthetics protect against organ injuries during and/or after surgery although it has always been debatable. Some papers suggest that volatile anesthesia may produce more myocardial protection compared to propofol 48 – 51 . Conversely, propofol was also reported to provide comparable myocardial protectivity like that of isoflurane in patients undergoing coronary artery bypass graft surgery 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is clinical evidence showing that general anesthetics protect against organ injuries during and/or after surgery although it has always been debatable. Some papers suggest that volatile anesthesia may produce more myocardial protection compared to propofol 48 – 51 . Conversely, propofol was also reported to provide comparable myocardial protectivity like that of isoflurane in patients undergoing coronary artery bypass graft surgery 52 .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of volatile anesthetic agents on outcome in cardiac surgery remains a topic of debate [40]. Özarslan et al compared the effect of various volatile anesthetics agents on sublingual microcirculatory perfusion and showed that sevoflurane compared to isoflurane and desflurane reduced microcirculatory perfusion during cardiac surgery, as reflected by a significantly lower PPV in small vessels during CPB.…”
Section: Cabg With Mecc -~Mfi -~Mfi --mentioning
confidence: 99%
“…In 2006, two meta-analyses of randomized controlled trials (RCTs) suggested that volatile anesthetics were not associated with reduced mortality when compared with total intravenous anesthesia (TIVA) in CABG surgery [8,9]. On the other hand, meta-analyses published later have shown a reduced mortality associated with volatile anesthetics in CABG surgeries [1014]. Finally, both the guideline from the American College of Cardiology/American Heart Association (ACCF/AHA) and the guideline from the European Association for Cardio-Thoracic Surgery (EACTS) have recommended the use of volatile anesthetics in patients undergoing CABG surgery [15,16].…”
Section: Introductionmentioning
confidence: 99%